Development of inspection systems for estimating the structural integrity of trees - Bellows, Curtis Charles (2008)
Urban tree managers are charged with the responsibility of managing large tree populations while securing a safe environment. A conflict exists between the presence of urban trees and the potential hazards these trees can be to buildings, vehicles, and inhabitants. Determining the structural stability of urban trees for the purpose of maintaining public safety is a chief function of urban forestry.